A Review of CO2 Electroreduction to Ethanol: C–C Coupling Mechanistic Insights and Catalyst Design - Zhao, Fang; Huang, Bo; Zhang, Yingzheng; Wei, Tianxin; Zhang, Jiatao; Zhao, Di (Nano-Micro Letters, 2026)
As a major contributor to climate change, CO2 has imposed severe detrimental effects on global ecosystems. Among various CO2 conversion strategies, the electrocatalytic CO2 reduction reaction (eCO2RR) stands out due to its ability to operate under mild conditions using renewable electricity. Compared to gaseous C2 products such as ethylene, ethanol as a liquid fuel demonstrates greater economic potential and broader market prospects. In recent years, copper-based electrocatalysts have emerged as leading materials for the electrochemical conversion of CO2-to-ethanol. Meanwhile, a number of non-copper-based electrocatalysts have also been developed to produce ethanol via C–C coupling pathways distinct from those on Cu-based materials. However, few reviews have systematically addressed the reaction mechanisms and material design principles specific to ethanol production through eCO2RR. In this review, we highlight the most recent advancements in this field of study. We begin by assessing the economic viability of ethanol as a CO2 reduction product. This is followed by a systematic summary of the reaction mechanisms and advanced characterization methods involved in ethanol production via eCO2RR across various pathways. Next, we discuss and compare the catalytic active sites and key electrochemical performance metrics for ethanol generation on different types of electrocatalysts. Finally, we propose several promising strategies to guide the rational design and synthesis of next-generation high-performance electrocatalysts for selective ethanol production. This review comprehensively summarizes the latest research progress in the field of ethanol production via eCO2RR from multiple dimensions, including the economic value of ethanol, reaction mechanisms, an introduction to various electrocatalysts and strategies for improving electrocatalysts. It not only promotes in-depth basic research, but also provides theoretical guidance for electrocatalyst design, reaction condition optimization, and industrial applications, making it of great research value and practical significance. Highlights: 1 Focusing on the economic viability of ethanol products and the application value of eCO2RR, this research anchors its core from an industrial conversion perspective, combining academic depth with practical orientation. 2 Systematically integrating multipath reaction mechanisms, advanced characterization techniques, and the active sites and performance metrics of various electrocatalysts, a comprehensive knowledge framework has been established. 3 Proposing a rational design strategy for next-generation highly selective ethanol synthesis electrocatalysts, this work provides a clear research direction for this field.